Exploring Strategies of Teaching Speaking among Indonesian and Malaysian Secondary English Teachers - Widiati, Utami; El Khoiri, Niamika; Nindya, Meyga Agustia; Sharif , Tengku Intan Suzila Tengku (Register Journal, 2023)
The current study aims at exploring strategies of teaching speaking among EFL/ESL teachers in Indonesian and Malaysian secondary schools. The data were obtained from 55 Indonesian teachers and 9 teachers from Malaysia, who were asked to voluntarily fill out an open-ended questionnaire consisting of 11 items. The questions ranged from teaching strategies to challenges in teaching speaking and the use of IT in the classroom setting. The findings of the descriptive analysis showed that teachers in both countries used relatively similar strategies, except for the aspect regarding the proportion of English use in the classroom. In this case, Malaysian teachers used English most of the time in their speaking class, compared to their Indonesia counterparts who admitted using L1 in various proportions and/or situations. It can be safely assumed that the status of English in Indonesia and Malaysia (EFL vs. ESL) is responsible for this difference, with Malaysian teachers and students being more comfortable with the use of English in their daily encounters.